Fears of school-age children and parental perceptions of nursing support during hospitalization in a selected pediatric hospital, Mangalore - Helma Maria Monteiro; Asha P Shetty; Praveen V Bagali (Wolters Kluwer Medknow Publications, 2014)
Background: A child's hospitalization is usually an unpleasant and difficult experience, both for the child and parents. Unfamiliarity of the environment, uncertainty regarding outcomes, and painful procedures are just a few stressors during hospitalization that can create overwhelming anxiety for children and their parents. Objectives: The objectives of the study were to assess the fears of school-age children during their hospitalization, assess parental perceptions of nursing support during their child's hospitalization, and to find association between children's fear and selected variables. Materials and Methods: To accomplish the objectives of the problem under study, nonexperimental typical descriptive design was adopted. The study was conducted in Regional Advanced Pediatric Care Center, Mangalore with the sample size of 60 hospitalized school-age children and their parents. Non-probability purposive sampling technique was used to select the sample. The researcher used background proforma for children and parents, Modified Child Medical Fear Scale and Modified Nurse Parent Support Tool to collect data from hospitalized school-age children and their parents, respectively. The tools were assessed for their reliability with the similar sample and found reliable. Informed consent was obtained from the study subjects. Results: Majority of the school-age children (91.67%) had moderate fear and 8.33% had high fear of hospitalization. Majority (70%) of parents have perceived fully satisfactory nursing support and 30% were satisfied with nursing support provided during their child's hospitalization. There was no significant association between the fears and selected demographic variables such as age of the child, gender, number of days of hospitalization, and previous experience of hospitalization. There was no significant difference between the fears in different age-groups of hospitalized school-age children to the different areas of fear in the hospital, i.e., environmental, procedural, interpersonal, and intrapersonal fears. Conclusion: Nurses should encourage children to express their fears and discuss their coping strategies. Nurses can promote the quality of family-centered care and should be aware of the importance of the several types of nursing support in meeting the requests of parents.